Banana streak virus: a unique virus-Musa interaction?: Proceedings of a workshop of the PROMUSA Virology working group, 19-21 January 1998, Montpellier, France - Frison, Emile A.; Sharrock, Suzanne L. (1998)
This workshop indicated that significant progress has recently been made, leading to the current thinking that three forms of banana streak virus (BSV) exist. It also showed that many questions remain to be answered and that a significant research effort has to be undertaken concerning transmission of the virus and detection methods.